Ezetimibe: An Unusual Suspect in Angioedema - Tiffany Lu; Tarundeep Grewal (Case Reports in Medicine)
We describe a case of new onset angioedema likely due to Ezetimibe therapy in an elderly patient with a prior history of drug-induced bradykinin reactions who had been on the medication for multiple years. This is the second reported incidence of Ezetimibe-associated angioedema in literature. A 90-year-old African American female presented with angioedema of the face and oral mucosa with associated difficulty speaking developing hours after taking Ezetimibe 10 mg PO. She denied adding any new or unusual foods to her diet. A thorough clinical history determined Ezetimibe was the likely culprit. Ezetimibe was immediately discontinued. The swelling subsided after administration of methylprednisolone 125 mg, epinephrine 1 mg/mL, injection 0.3 mL, diphenhydramine 25 mg, and famotidine 20 mg BID within 48 hours. The patient’s C1 esterase inhibitor level was measured to be within normal limits. Food panel allergy testing showed very low or undetectable IgE levels in all categories. Based on the limited reports in literature and our current case, we conclude that there is a likely association of angioedema with Ezetimibe. The mechanism, however, is unknown since it is not related to bradykinin or mast cell-mediated activation. Clinicians should advise patients taking Ezetimibe to report any swelling of the lips, face, and tongue and to immediately discontinue its use if these signs are present.